The New Line of the European Union in Migration Domain: Emphases And Mechanisms - L. Sadykova (Международная аналитика, 2016)
Article is devoted to complex research of new mechanisms of the European migration policy which underwent essential changes in process of increase of migratory streams. Now its main components are strengthening of measures against illegal migration, support of legal migration (in particular, simplification of entrance for highly qualified specialists), integration of already arrived migrants into West European society. Though migration policy is still one of the cornerstones of the general foreign policy of EU countries, legal regulation of illegal migration still fully doesn’t answer modern realities.